Perinatal Nutritional Reprogramming of the Epigenome Promotes Subsequent Development of Nonalcoholic Steatohepatitis. Issue 12 (1st October 2018) - Gutierrez Sanchez, Luz Helena; Tomita, Kyoko; Guo, Qianqian; Furuta, Kunimaro; Alhuwaish, Husam; Hirsova, Petra; Baheti, Saurabh; Alver, Bonnie; Hlady, Ryan; Robertson, Keith D.; Ibrahim, Samar H.
Abstract : With the epidemic of obesity, nonalcoholic fatty liver disease (NAFLD) has become the most common pediatric liver disease. The influence of a perinatal obesity‐inducing diet (OID) on the development and progression of NAFLD in offspring is important but incompletely studied. Hence, we fed breeding pairs of C57BL/6J mice during gestation and lactation (perinatally) either chow or an OID rich in fat, fructose, and cholesterol (FFC). The offspring were weaned to either chow or an FFC diet, generating four groups: perinatal (p)Chow‐Chow, pChow‐FFC, pFFC‐Chow, and pFFC‐FFC. Mice were sacrificed at 10 weeks of age. We examined the whole‐liver transcriptome by RNA sequencing (RNA‐seq) and whole‐liver genome methylation by reduced representation bisulfite sequencing (RRBS). Our results indicated that the pFFC‐FFC mice had a significant increase in hepatic steatosis, injury, inflammation, and fibrosis, as assessed histologically and biochemically. We identified 189 genes that were differentially expressed and methylated in the pFFC‐FFC mice versus the pChow‐FFC mice. Gene set enrichment analysis identified hepatic fibrosis/hepatic stellate cell activation as the top canonical pathway, suggesting that the differential DNA methylation events in the mice exposed to the FFC diet perinatally were associated with a profibrogenic transcriptome. To verify that this finding was consistent with perinatal nutritional reprogramming of the methylome, we exposed pFFC‐Chow mice to an FFC diet in adulthood. These mice developed significant hepatic steatosis, injury, inflammation, and more importantly fibrosis when compared to the appropriate controls. Conclusion : Perinatal exposure to an OID primes the immature liver for an accentuated fibrosing nonalcoholic steatohepatitis (NASH) phenotype, likely through nutritional reprogramming of the offspring methylome. These data have potential clinical implications for monitoring children of obese mothers and risk stratification of children with NAFLD. Abstract : Perinatal exposure to high fat, fructose, and cholesterol (FFC) in mice primes the fetal liver to fibrosing NASH, likely secondary to nutritional reprograming of the liver methylome. This association is further confirmed, upon re‐exposure to the FFC diet in adulthood, where mice develop an accentuated, rapidly progressive NASH phenotype.